Organizing the 20th-century world : international organizations and the emergence of international public administration, 1920-1960s - Gram-Skjoldager, Karen; Ikonomou, Haakon A.; Kahlert, Torsten, 1977- (London ; New York : Bloomsbury Academic, 2020)
"A historical and methodological exploration of International Organizations as a new form of political power between the 1920s and 1960s"--
Includes bibliographical references and index.
Keywords: International agencies -- History -- 20th century; International agencies -- Political aspects; Print books